Graphene aerogel and its composites: synthesis, properties and applications - Kasar, Ashish K.; Tian, Siyu; Xiong, Guoping; Menezes, Pradeep L. (Journal of porous materials, 2022)
Graphene is an attractive material for many applications due to excellent inherent properties such as lower density, high mechanical strength, higher thermal conductivity, etc. However, it has been used as an additive material due to size limitation. To overcome the size limitation without affecting the inherent properties of 2D graphene sheets, researchers have developed graphene aerogel (GA) by different synthesis techniques. GA has become an emerging light-weight structure in the group of aerogel materials because of various applications. In this review article, the mechanical properties of GA have been discussed by considering the structural parameters of GA, such as pore size, graphene sheet alignments, and wall thickness, because the mechanical performance of the GA is an important criterion prior to its application in any field. It has also been highlighted that the structural parameters can be altered during synthesis to achieve desired mechanical properties. Applications of GA have been thoroughly discussed in the field of polymer composites and how GA-polymer structures can help to generate a cleaner environment by separating spilled oil from water and removing organic pollutants from water. In addition, potential of GA for various other applications with suitable nano material additives have been highlighted.